Characterization of 2,3,7,8-Substituted Chlorodibenzo-p-dioxins using LRGC-MS/MS - THACKER, N.P.; NITNAWARE, V.C.; PANDYA, G.H.; DESHPANDE, V. (Asian Journal of Chemistry, 2010)
Exquisitely sensitive and specific GC-MS capable of resolving low levels of dioxins and potential toxic congeners in environmental matrices is must. The work aims to resolve the most toxic 2,3,7,8-substituted dibenzo-p-dioxins in soil sample by low resolution gas chromatography coupled to ion-trap mass spectrometry (LRGC-MS/MS). In particular, the study mainly focuses on simple and efficient method for analyzing 2,3,7,8-tetrachlorodibenzo-p-dioxins (2,3,7,8-TCDD) using different extraction methods. This paper illustrates optimization steps required for 2,3,7,8-TCDD analysis using LRGC-MS/MS. Finally, quality control measures include the calibration exercises. Successful results were achieved using LRGC-MS/MS in the analysis of simulated soil samples. In general, LRGC-MS/MS in conjunction with rotatory shaker extraction method constitutes an interesting and simple alternative for routine analysis of such matrices.